Thrombospondin expression in myofibers stabilizes muscle membranes - Davy Vanhoutte; Tobias G Schips; Jennifer Q Kwong; Jennifer Davis; Andoria Tjondrokoesoemo; Matthew J Brody; Michelle A Sargent; Onur Kanisicak; Hong Yi; Quan Q Gao; Joseph E Rabinowitz; Talila Volk; et al. (eLife, 2016)
Skeletal muscle is highly sensitive to mutations in genes that participate in membrane stability and cellular attachment, which often leads to muscular dystrophy. Here we show that Thrombospondin-4 (Thbs4) regulates skeletal muscle integrity and its susceptibility to muscular dystrophy through organization of membrane attachment complexes. Loss of the Thbs4 gene causes spontaneous dystrophic changes with aging and accelerates disease in 2 mouse models of muscular dystrophy, while overexpression of mouse Thbs4 is protective and mitigates dystrophic disease. In the myofiber, Thbs4 selectively enhances vesicular trafficking of dystrophin-glycoprotein and integrin attachment complexes to stabilize the sarcolemma. In agreement, muscle-specific overexpression of Drosophila Tsp or mouse Thbs4 rescues a Drosophila model of muscular dystrophy with augmented membrane residence of βPS integrin. This functional conservation emphasizes the fundamental importance of Thbs’ as regulators of cellular attachment and membrane stability and identifies Thbs4 as a potential therapeutic target for muscular dystrophy.